The State As a Non-Cooperative Equilibrium - Flavio Delbono; Gianluca Fiorentini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
We propose a theory of the origin of the State as an institution originating from the voluntary interaction among decentralized and fully informed agents.
Keywords: 330